Respuesta :

Answer : 30 units squared

Multiply 6 by 10, then divide by 2.



[tex] {10}^{2} - {6}^{2} = {(the \: entire \: triangles \: height}^{2} \\ = 100 - 36 \\ = 64 = {(the \: entire \: triangles \: height}^{2} \\ this \: means \: the \: entire \: triangles \: height \: = 8 \\ \\ now \: {17}^{2} - {8}^{2} \\ = {(the \: length \: of \: the \: base \: of \: the \: left \: triangle)}^{2} \\ \\ so \: {17}^{2} - {8}^{2} = 225 \\ = {(length \: of \: the \: base \: of \: the \: left \: triangle)}^{2} so \\ the \: length \: of \: the \: base \: of \: the \: left \: triangle \: = 15 \\ \\ the \: base \: of \: the \: triangle \: is \: 15 + 6 = 21 \: and \: its \: height \: is \: 8 \\ \\ the \: triangles \: are \: is \: \frac{1}{2} \times base \: \times height \\ = \frac{1}{2} \times 21 \times 8 = 84[/tex]